Community participation and operational lessons from implementing a protective coating as a novel vector control tool in dengue-endemic neighborhoods of Cúcuta and Los Patios, Colombia - Susana Koo Chong; María Angelica Carrillo; Rocío Cárdenas Sánchez; Tatiana Rivera-Ramirez; Axel Kroeger (BMC Public Health, 2026)
Abstract Background The control of Aedes-borne diseases (dengue, Zika, chikungunya, yellow fever) is a high public health priority in tropical and subtropical countries. The adoption of new vector control tools, such as protective coating (PC), requires understanding the social dynamics that influence their acceptance and feasibility. This study investigated the experiences and perspectives of diverse stakeholders involved in a vector control project in urban Colombia, with the aim of assessing community acceptance and operational feasibility. Insights gained are important for optimizing implementation and gauging the broader viability of innovative vector control strategies. Methods A qualitative descriptive study was conducted using focus group discussions and in-depth interviews with 70 key stakeholders, including community leaders ( n = 3), community volunteers ( n = 30), vector control staff ( n = 7), supervisors ( n = 5), and community residents ( n = 25). Data was collected after the intervention and analyzed using inductive thematic content analysis with open coding. Participation was voluntary and confidential. Results The protective coating was perceived as feasible and generally well accepted by the community. Facilitating factors included the involvement of community leaders, strong volunteer commitment, and effective coordination among institutions. Challenges such as trust issues, logistical constraints, and safety concerns were identified and addressed through adaptive strategies, including adjusted work schedules and strengthened communication. Conclusion Community involvement, effective communication, and adaptive management were key to the successful implementation of the protective coating and helped address logistical challenges. The lessons learned provide useful information for scaling up novel vector control approaches in similar urban settings in Latin America.